Роль викладачів Львівської політехніки у польових дослідженнях археологічних пам’яток України - Терський, Святослав; Гусак, Ярина; Tersky, Sviatoslav; Husak, Yaryna (Видавництво Львівської політехніки, 2020)
Проаналізовано участь викладачів Львівської політехніки у польових дослідженнях археологічних пам’яток України протягом другої половини XIX ст. – початку XX ст., а також на початку XXI ст. З’ясовано, що головними об’єктами зацікавлень дослідників-архітекторів були храми княжих столиць – Львова, Галича та Холма. Дослідники-геологи цікавилися стоянками палеоліту. Показано, що важливою причиною відновлення археоло- гічних досліджень у Львівській політехніці була поява нових навчальних спеціальностей.

The participation of teachers of Lviv Polytechnic in field research of archeological monuments of Ukraine during the second half of XIX century – beginning of XX century and also at the beginning of XXI century is analyzed. It was found that the main objects of interest of researchers-architects were the temples of princely capitals – Lviv, Halych and Cholm. The first rector of Lviv Polytechnic, architect Julian Zakharievich (1837–1898), was especially distinguished in this activity. From the 1880s he worked as a correspondent for the Central Commission for the Study and Conservation of Monuments of Art and History, and then worked as a conservator of historical monuments, within the organization of the Circle of Imperial and Royal Conservatives and Correspondents of Galicia” established in 1888. In 1882 together with the professor of the University of Lviv I. Sharanevich and the priest L. Lavretsky of the village. In the chronicle of Halych, he excavated the foundations of three stone temples of the 12th – 13th centuries. Architects of Lviv Polytechnic Yu. Zakhariyevich, I. Levinsky, V. Sadlovsky, and I. Obminsky also explored the medieval Lviv hills in the process of restoration works. Geological researchers were interested in Paleolithic sites. The head of the Museum of Mineralogy and Geology of the Polytechnic School in Lviv, Professor Tadeusz Wisniewski (1865–1933), carried out a study of the Paleolithic site found in Gliniany of the Przemysliany County. The remains of mammoths and numerous silicon implements were discovered there. It is shown that the emergence of new educational specialties was an important reason for the renewal of archaeological research in Lviv Polytechnic. The most important archaeological excavations of the early XXI century. were investigations of the foundations of the Church of the Blessed Virgin Mary, built in the Cholm by King Danylo Halytskyi, and exploration of multiple times monuments in Lviv region.
The role of the lecturers of the Lviv polytechnics in the field research of archaeological monuments of Ukraine
Keywords: Львівська політехніка; викладачі; археологічні пам’ятки; храми; палеолітичні стоянки; Lviv Polytechnic; teachers; archeological sites; temples; Paleolithic sites; 902(477.83)